Improving Parenting Practices Among Fathers Who Misuse Opioids: Fathering Through Change Intervention - Cioffi, Camille C.; DeGarmo, David S. (Frontiers in Psychology, 2021)
Fathers have been largely neglected in the parenting literature though there is a critical need to improve parenting practices among fathers who misuse opioids in the midst of the opioid epidemic. Urgency is critical to rapidly intervene in the lives of fathers and children to reduce misuse and interrupt intergenerational cycles of substance misuse. Thus, we provide an overview of solutions to adapt existing parenting interventions for fathers who misuse opioids to accelerate the pace of science for this population.